2020
DOI: 10.1177/1940082920917825
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Monitoring of Jaguar (Panthera onca) in the Chinantla Region, Mexico

Abstract: Successful community-based wildlife monitoring necessitates a high degree of local participation during sampling design and data collection. Here, we describe a community-based monitoring framework to estimate density and habitat use of the threatened jaguar (Panthera onca) in tropical montane forests in the Chinantla region of Oaxaca, Mexico. Community-based monitoring was completed involving integration with local communities, local governmental agencies, nongovernmental organizations, and academic instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Although local-scale factors can affect jaguar densities, and we have shown that multiple opposing factors shape jaguar spatial needs, there was a correlation between home range size and densities within our study ecoregions (Figure S1) as would be expected based upon energetic limits. 16 Similarly, the relationship between densities in other regions 41,[45][46][47][48][49] and home range size is evident in the range-wide predictions of our model (Figure 4) where increasing estimated densities corresponded to increasing predicted relative home range size. However, as our predictions are based upon mean predicted effects, their representation of areas for which we did not have data needs to be interpreted cautiously, especially for humid forests, given the aforementioned potential bias stemming from the availability of terrestrial prey biomass in these systems.…”
Section: Home Range Sizesupporting
confidence: 58%
“…Although local-scale factors can affect jaguar densities, and we have shown that multiple opposing factors shape jaguar spatial needs, there was a correlation between home range size and densities within our study ecoregions (Figure S1) as would be expected based upon energetic limits. 16 Similarly, the relationship between densities in other regions 41,[45][46][47][48][49] and home range size is evident in the range-wide predictions of our model (Figure 4) where increasing estimated densities corresponded to increasing predicted relative home range size. However, as our predictions are based upon mean predicted effects, their representation of areas for which we did not have data needs to be interpreted cautiously, especially for humid forests, given the aforementioned potential bias stemming from the availability of terrestrial prey biomass in these systems.…”
Section: Home Range Sizesupporting
confidence: 58%
“…Our study used a community-based monitoring framework to survey the large mammal fauna at multiple sites over a 10-year period. By empowering local partners to monitor the camera trap surveys, this approach enabled us to capture long-term data from remote sites comparable to that collected by professional scientists ( Danielsen et al 2014 ) while at the same time providing social benefits from increased engagement of local communities in wildlife conservation ( Danielsen et al 2014 ; Lavariega et al 2020 ). Compared with top-down attempts to regulate hunting, community-based conservation approaches that emphasize environmental education, citizen science, and the socio-economic benefits of sustainable development offer a more comprehensive road to reduced hunter defaunation that can maintain the biodiversity and community structure of tropical forest systems.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling protocol. We followed the community-based framework for camera-trap studies proposed by Lavariega et al (2020). This approach involves engaging a number of actors, including government staff of the protectedarea system, community monitors (local people previously trained in biodiversity studies), non-governmental organizations, and academic institutions, aiming to exchange knowledge and experience, make decisions on sampling design, participate in data collection, and discuss and communicate the results.…”
Section: Methodsmentioning
confidence: 99%